Everywhere blue - Rossmassler Fritz, Joanne (Holiday House, 2021)
Twelve-year-old Maddie, who suffers from anxiety, loves music, math, and everything in its place, but when her older brother Strum disappears from his college campus, her family starts slipping away from her.